ЛАЗАРСКИТЕ ОБРЕДНИ ФОРМИ И ДЕЈСТВИЈА, ИЗРАЗ НА ЖЕНСКАТА ПУБЕРТЕТСКА ИНИЦИЈАЦИЈА НА ПРЕМИН - НИЗ ПРИМЕРИ ОД МАКЕДОНСКИОТ ФОЛКОР (Filološke studije, 2019)
Realizing the aspects of Lazarus as female puberty rites of passage, in which the change of status of the participants can be seen in the entire development pipeline: the phase when young sexually mature girls can enter the group of Lazarus up to the moment when he performed the role of the main Lazarus, completes the cycle of their sexual maturation. From that moment candidates - main lazarius who successfully passed this initiation ritual, acquire the status of girl ready for wedding, by its function marks the transition to another social category - that of adults. The culmination of this transition will be a ritual of marriage, which will be fully completed cycle of female puberty and entering the world of adults. Numerous elements identified in this ritual, which bear traces of ancient pre-Christian initiation rites as part of the Spring agrarian calendar cycle of holidays, attest to the ancient roots of the initiation rites of premiums integral part of Macedonian traditional culture.